Mapping global trends in Lamiaceae research - Roma, K; Manisha, A P; Saloni, G; DoCharu, D R; Jasleen, K (Plant Science Today, 2026)
This study presents a comprehensive bibliometric analysis of global scientific literature on the family Lamiaceae , commonly known as the mint family. The primary objective is to systematically map the research landscape, identify key trends, highlight influential entities and uncover emerging themes within this diverse botanical group. Data were meticulously retrieved from major scientific databases, including Scopus and Web of Science, covering publications from 1954 to 2025. Advanced bibliometric tools such as VOSviewer, Bibliometrix R and CiteSpace were employed to conduct performance analysis and science mapping, including co-authorship, co-citation and co-word analyses. A total of 2145 documents were analyzed, showing a 6.75 % annual growth rate and strong collaboration between China, India and Iran. The analysis reveals a dynamic research field characterised by distinct periods of significant growth, with notable surges in publication activity observed from 2006 to 2012, particularly in studies focusing on Orthosiphon stamineus, a prominent species within the family Lamiaceae. Core research areas predominantly focus on the pharmacological properties of Lamiaceae species, including their antidiabetic, antioxidant, anti-inflammatory, neuroprotective and pesticidal activities. Additionally, substantial attention is given to phytochemical characterisation and ethnobotanical applications. The study identifies leading journals, prolific authors and dominant contributing countries, while collaboration networks and thematic clusters underscore the field's interdisciplinary nature and evolving research focus. The findings highlight the immense medicinal and economic potential of Lamiaceae, emphasising the need for sustainable practices and continued exploration of its rich array of bioactive compounds. This analysis provides a strategic roadmap for future research, identifying current knowledge gaps and highlighting promising avenues for novel discoveries.